Strategi Pemasaran di Media Sosial untuk Membangun Reputasi dan Eksistensi Pondok Pesantren - Riskiyah, Eka Maftuhatil; Mentari, Inggi Eka Ria; Jannah, Revi Rusdatul; Winarsi, Putrri (PRoMEDIA, 2024)
Marketing is a crucial thing for educational institutions such as Islamic boarding schools. Every Islamic boarding school needs marketing to maintain its existence in society. This study was conducted to find a marketing strategy based on information and communication technology through social media. The research method used is descriptive qualitative research with observation data collection, questionnaires and literature reviews. The results of the study are: 1. Marketing based on information and communication technology is very important to be carried out in Islamic boarding schools through the stages of planning, organizing, implementing and evaluating. 2. Utilization of social media such as Instagram and YouTube as a marketing strategy. 3. The implications of using Social Media can increase public awareness and can provide a positive image for institutions and increase public interest.Keywords: Educational Marketing, Information And Communication Technology, Social Media, Islamic Boarding Schools